TRADE OPENNESS AND ECONOMIC GROWTH NEXUS: AN IMPACT ANALYSIS OF NIGERIAN ECONOMY - Elijah, Sunday; Zoramawa, Lawali Bello (IJRDO - Journal of Social Science and Humanities Research, 2018)
ABSTRACT Theoretically, it was established that outward oriented economies grow faster than closed economies and could achieve a respectable level of economic development. This study is set out to examine empirically the impact of trade openness on economic growth in Nigeria between 1980 and 2016. Data were sourced from publications of the central bank of Nigeria (CBN) statistical bulletin 2016. The econometric techniques used in the analysis were: unit root test, Johansen cointegration test, and error correction models (ECM). From the analysis, results revealed that openness was found to have impacted negatively on economic growth in both the long-run and the short-run. Based on this finding it is recommended that since the country’s imports are greater than exports; there is the need for the government to sustain its current efforts in diversifying the economy in order to achieve exports led economic growth. Furthermore, the government through collaborative effort with the private sector should encourage Export Substitute Industries in the country in order to promote export and to discourage the importation of primary commodities especially in which the nation has absolute advantages. Finally, the study further recommended that government should retain the current policy of treasury single account (T.SA) in order to block the loopholes in both the public and the private sectors and to ensure equitable utilization of the internally generated revenues for the benefit of the masses. Keywords: Economic Openness, Import, Export, Economic Growth, ARDL. JEL: F19, F43,O24